Driving Photocatalytic Efficiency through Controlled Cobalt–Iron and Cobalt–Nickel Ratios for Methylene Blue Degradation - Ulfa, Maria; Rohmah, Istinganah Saestu; Anggreani, Cindy Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
This study explores the development of nanostructured photocatalytic materials based on cobalt–iron (CoFe1-2) and cobalt–nickel (CoNi1-1) systems for the degradation of methylene blue, a persistent organic pollutant commonly found in textile wastewater. As the textile industry contributes significantly to environmental pollution through the discharge of recalcitrant dyes, this work aims to offer an effective and sustainable solution via visible-light-driven photocatalysis. The synthesis strategy employed a hard-template approach using mesoporous silica-gelatin composite (SPG-20), prepared from a mixture of P123 and gelatin under acidic conditions. Following hydrothermal treatment and calcination, the SPG-20 template was acid-activated to enhance surface reactivity. Metal precursors—Co(NO₃)₂.6H₂O with either Fe(NO₃)₃.9H₂O or Ni(NO₃)₂.6H₂O—were infiltrated into the template with citric acid as a chelating and carbon-forming agent. The composite underwent controlled thermal treatment to embed metal species into a confined carbon matrix, followed by alkaline etching to remove the silica scaffold and yield CoFe1-2 and CoNi1-1 carbon nanostructures. Comprehensive characterizations, including XRD, FTIR, BET, UV-DRS, and UV–VIS spectroscopy, revealed that the materials exhibited nanocrystalline domains with low crystallinity and high specific surface area, favorable for photocatalytic activity. BET analysis indicated a greater surface area in CoFe1-2 (104.526 m²/g) than in CoNi1-1 (83.160 m²/g), correlating with a higher number of available active sites. The band gap of CoFe1-2 (1.180 eV) supports efficient visible-light absorption, which, coupled with its higher microporosity, enables superior methylene blue degradation (85% within 90 minutes) compared to CoNi1-1 (75%). Control experiments in the absence of light showed minimal degradation, confirming that the reaction is photocatalytic in nature. Adsorption kinetics followed a pseudo-first-order model, with CoFe1-2 also exhibiting a higher adsorption capacity (171.184 mg/g). These findings demonstrate the potential of template-assisted synthesis in producing tunable, high-performance photocatalysts for practical applications in sustainable textile wastewater treatment. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).